2015
DOI: 10.1016/j.ijpp.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Differences in Accidental Trauma to Upper and Lower Limb Bones at Aquincum, Roman Hungary

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…The present data illustrate that in comparison to other Late Antique commonly seen in accidents (Gilmour et al, 2015). Both collisions and falls can lead to such injuries (Lewis, 2012;Porta, 2005;Rowbotham & Blau, 2016).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The present data illustrate that in comparison to other Late Antique commonly seen in accidents (Gilmour et al, 2015). Both collisions and falls can lead to such injuries (Lewis, 2012;Porta, 2005;Rowbotham & Blau, 2016).…”
Section: Discussionsupporting
confidence: 62%
“…Various authors argue that the predominance of observed bone damage relates to injuries obtained through accidents associated with daily activities with high trauma risk factors (Gerhards, 2007;. Bioarchaeological research by Gilmour et al (2015), Mant (2019) and Myszka et al (2012) show that a significant amount of bone trauma is attributable to labour-related accidents. However, as shown in the literature (e.g., Caffell & Holst, 2012;Šlaus et al, 2012;Smith, 2017), violence-related trauma seems to be common in past societies, especially during periods of political changes.…”
Section: Introductionmentioning
confidence: 99%
“…Bone is a dynamic tissue with the ability to remodel and as such, in the case of healed trauma, it is most often impossible to estimate at what age an individual suffered an injury. In addition, when the skeleton of an individual exhibits multiple healed traumas it is extremely difficult, if not impossible, to ascertain if the injuries were sustained in one traumatic event or over the person’s lifetime [44]. In human skeletal remains, the bones fractured, distribution of injuries, types of fracture lines, and associated cultural context can help to interpret the mechanism of injury in the past [34].…”
Section: Methodsmentioning
confidence: 99%
“…Shape analyses have also been used to evaluate therapeutic interventions, their application, and (lack of) success in the past. Angulation, rotation, and overlap at healed fracture sites are investigated by Grauer and Roberts (1996), Judd and Roberts (1999), and Gilmour et al (2015) who recorded the amount of malunion (i.e., angulation, apposition, overlap, rotation) present between the segments of healed long‐bone fractures. This information is typically used to comment on the absence or unsuccessful nature of fracture treatment (interpretations based on data collected on modern humans by Roberts, 1988).…”
Section: Shape In Palaeopathological History: a Meta‐analysismentioning
confidence: 99%